ESTUDO SOBRE O RELACIONAMENTO ENTRE OS ÓRGÃOS E AGÊNCIAS REGULADORAS E O INMETRO: FOCO NAS ATIVIDADES DE AVALIAÇAO DA CONFORMIDADE - Martinelli, Maria Aparecida (2009)
The development of conformity assessment programs by the Directorate of Quality of Inmetro is an activity which causes impacts in distinct sectors of society and involves partnerships with many governmental agencies and ministries in the field of mandatory conformity assessment programs. In some situations, these institutions develop their own conformity assessment programs without availing themselves of the use of the third-party infrastructure already available in the Brazilian Conformity Assessment System a part of Sinmetro that is managed by Inmetro. This work presents an approach to evaluate the perceptions and the gaps in perceptions between two distinct groups, one comprised of technicians and managers of the Directorate of Quality of Inmetro and the other comprised of technicians and managers of governmental agencies and ministries in regard to the role and conformity assessment service developed by Inmetro. In the context of this work, the mapping and the identification of the gaps of perceptions about the performance of Inmetro as a manager of conformity assessment programs and its interactions with the governmental agencies and ministries provide elements upon which to define/build strategies that will help in the improvement and the management of this service. The information used in this paper has been collected from the responses of 55 technicians and managers of two distinct groups to a structured questionnaire. This questionnaire focused on issues involving the performance as well as the role of Inmetro in the development of conformity assessment programs. Following a review of the responses, itwas verified that the respondents: (1) highlighted the partnership with Inmetro as valuable; (2) presented proposals whereby Inmetro could enhance its service; and (3) at the same time, set forth some reasons that impede conformity assessment partnerships with Inmetro.